Application of Detergent as Enhancer in Cassava Flour Processing: A Threat to Life - Hikon, B.N; Dewa, Abubakar Umar; Jonathan, Nelson; Vincent, P. (Darul Yasin Al Sys, 2024)
Introduction: Cassava flour is a processed product from Cassava tuber (Manihot esculenta Crantz) as a staple food, it is a major source of carbohydrate. Due to effects of climate related variables (dry and rain season) on the production and processing of cassava, rural dwellers have adopted the practice of using detergent (linear alkyl benzene sulfonate, LABS) to enhance the process of fermentation of cassava. Purpose of the Study: The study on the application of detergent as enhancer in cassava flour processing: A threat to life was purposely designed to substantiate the assertion that, detergent are used to aid fermentation of cassava. Materials and Methods: Samples of cassava tubers were randomly collected from three (3) farms, they were peeled, washed and soaked in detergents of concentrations; 0.05g/L, 0.1g/L and 0.5g/L and their rates of fermentation and pH were monitored, a control (sample without detergent) was also set up for comparison. A total of three (3) cassava flour were obtained from Wukari market, North Eastern Nigeria and were subjected to the same analysis with other samples in the laboratory. All samples were characterized with Fourier Transform Infra-Red (FTIR), titrimetric method for residual detergent (LABS) and Flame photometer for Na concentrations. Results: The results obtained showed that the sample with least concentration of detergent (0.05 g/L) fermented within 48 hrs without objectionable odour, followed by 0.1 g/L at 54 hrs and 0.5 g/L at 68 hrs, the control sample fermented after 72 hrs with undesirable odour. The results of FTIR and Flame Photometer indicate the presence of Silicate, Azide and Na in both samples. Conclusion: The findings have proved that some of the Cassava Flour sold within Wukari Metropolis contained high concentration of residual LABS and sodium which have adverse effect on humans.